The Proceduralisation of Australian Corporate Law. (June 2015) - Grantham, Ross
The central hypothesis of the paper is that bit by bit and largely unnoticed Australian corporate law has undergone a profound change. Australian corporate law, and particularly the Corporations Act 2001 (Cth), has moved from an essentially private law, substantive rights model, to one that seeks to regulate the company and those involved in its affairs through the prescription of processes and procedures by which corporate decisions may be made and by which the procedural correctness of those decisions is assured. The paper will also seek to demonstrate, by an analysis of the changes in the patterns of corporate case law, that this proceduralising trend has effected a fundamental change in the nature of corporate law and the role of the courts and may now claim to be a, if not, the principal characteristic of Australian corporate law. The paper concludes by highlighting some of the wider implications of this trend and the risk it poses to the intellectual heart of corporate law. The modern registered company owes its immediate creation to the legislature. Historically, however, the nature of the corporate form and the content of what is now known in Australia as corporate law has been very much more the work of the courts. 1 It is thus the case that the decision of the House of Lords in Salomon v A Salomon & Co Ltd 2 is more often cited as the foundation of modern corporate law than are the Joint Stock Companies Act 1844 (UK) 3 or the Limited Liability Act 1855 (UK). 4 It is also the case that the building blocks of corporate law were predominantly taken from the private law. Within the open girders of the statutory framework, 5 corporate law was built out of the concepts of contract, property, and trust. It is thus not surprising that the company was, and is still, regarded as a fundamentally private legal and economic institution. 6